Perkembangan Pelaksanaan Urusan Pemerintahan Umum di Daerah: Studi terhadap Pelaksanaan Urusan Pembinaan Pancasila dan Wawasan Kebangsaan - Gani Wardhana, Allan Fatchan; Yuniar Riza Hakiki; Diva Febrina Nurcahyani Rahman (Fakultas Hukum Universitas Islam Indonesia, 2024)
General government affairs fall under the authority of the President as the head of Government, which in fact are carried out by Heads of the Region, one of which is the sub-affairs of developing the value Pancasila and the nationalism insight. This authority is in fact exercised by the Regional Government by establishing Regional Regulations (Perda). In fact, regional regulations are enacted in order to carry out government affairs which fall under regional authority, carry out regional autonomy and assistance tasks, and accommodate special regional conditions. This research examines two features, first, can the authority for general government affairs be divided between provinces and districts/cities? Second, how is the development of the implementation of authority for general government affairs in the regions? The research method used is normative juridical with a statutory and a conceptual approach. The results of this research are first, that although general government affairs are the authority of the President, their implementation is divided among the regions. The matter of fostering Pancasila and nationalism insight reaches all regions in Indonesia and is certainly not effective if it is only carried out by the President. Second, general government affairs which were originally carried out on the principle of deconcentration have developed towards decentralization. Strengthening the independence of Regional Governments in carrying out general government affairs is reason enough. Such as the formation of the Regional Regulation on Pancasila Education and National Insight which accommodates locality aspects and financing from the APBD. Regions in the implementation of general government affairs are ultimately not only administrative regions, but have become autonomous regions.Keywords: Fostering Pancasila; General Government Affairs; Nationalism Insight; Regional Affairs. AbstrakUrusan pemerintahan umum merupakan kewenangan Presiden sebagai kepala Pemerintahan yang faktanya dilaksanakan Kepala Daerah, salah satunya yaitu sub urusan pembinaan Pancasila dan wawasan kebangsaan. Kewenangan tersebut faktanya dilaksanakan oleh Pemerintahan Daerah dengan membentuk Peraturan Daerah (Perda). Padahal Perda dibentuk dalam rangka melaksanakan urusan pemerintahan yang menjadi kewenangan daerah, menyelenggarakan otonomi daerah dan tugas pembantuan, serta menampung kondisi khusus daerah. Penelitian ini mengkaji dua hal, pertama, apakah kewenangan urusan pemerintahan umum dapat dibagi ke daerah Provinsi dan Kabupaten/Kota? Kedua, bagaimana perkembangan pelaksanaan kewenangan urusan pemerintahan umum di daerah? Metode penelitian yang digunakan yaitu yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini yaitu pertama, urusan pemerintahan umum meskipun merupakan kewenangan Presiden, namun pelaksanaannya dibagi kepada Daerah. Urusan pembinaan Pancasila dan wawasan kebangsaan menjangkau seluruh wilayah di Indonesia dan tentu tidak efektif apabila hanya dilaksanakan oleh Presiden. Kedua, urusan pemerintahan umum yang semula dilaksanakan dengan asas dekonsentrasi telah berkembang mengarah ke desentralisasi. Menguatnya kemandirian Pemerintahan Daerah dalam melaksanakan urusan pemerintahan umum cukup menjadi alasan. Sebagaimana dibentuknya Perda tentang Pendidikan Pancasila dan Wawasan Kebangsaan yang mengakomodasi aspek lokalitas dan pembiayaan dari APBD. Daerah dalam pelaksanaan urusan pemerintahan umum pada akhirnya juga tidak hanya sebagai wilayah administratif, akan tetapi telah menjadi daerah otonom.Kata Kunci: Daerah; Pembinaan Pancasila; Urusan Pemerintahan Umum; Wawasan Kebangsaan.